Chronic opioid use in patients undergoing treatment for oropharyngeal cancer. (6th January 2019) - Silver, Natalie; Dourado, Justin; Hitchcock, Kathryn; Fullerton, Amy; Fredenburg, Kristianna; Dziegielewski, Peter; Danan, Deepa; Tighe, Patrick; Morris, Chris; Amdur, Robert; Mendenhall, William; Fillingim, Roger B.
Abstract : Objectives/Hypothesis: Head and neck cancer pain is a prevalent problem, and the current opioid crisis has highlighted concerns raised in chronic pain management. This study assessed the characteristics of opioid use in patients undergoing treatment for oropharynx cancer and identified risk factors associated with chronic opioid use. Study Design: Retrospective cohort study. Methods: A study was conducted of 198 eligible patients who underwent radiotherapy as part of their treatment for oropharynx cancer at a single institution from 2012 to 2017. p16/human papillomavirus (HPV) status was determined by pathology report review. Opioid use was recorded. Statistical analysis was performed to assess risk factors for chronic opioid use and effect on overall survival. Results: The average age was 62 years, and the mean follow‐up was 38 months. Eighty‐three percent of patients had stage III/IV disease, and 73% received chemoradiotherapy. Sixty‐nine percent were HPV/p16 positive. Fifty‐seven (29%) patients had preexisting chronic pain conditions. Chronic opioid use was observed in 53% of the patients. Age ≤ 62 years ( P < .0001), history of depression ( P = .0356), p16 negative status ( P = .0097), opioid use at pretreatment visit ( P = .0021), and presence of a preexisting chronic pain condition at time of diagnosis ( P = .0181) were associated with chronic opioid use using univariate analysis. On multivariate analysis, T stage and anxiety/depression were associated with chronic opioid use. Overall survival was worse for patients who had chronic opioid use, but was not significant when recurrence was taken into consideration. Conclusions: More than 50% of the patients treated for oropharynx squamous cell carcinoma in this cohort were chronic opioid users after treatment. Identifying patients at greatest risk for chronic opioid use prior to treatment may help with long‐term pain management in this patient population. Level of Evidence: 4 Laryngoscope, 129:2087–2093, 2019